Perkembangan Peserta Didik - Elisabeth Ellena Christy Ejune; Fadilah Nur Hanifah; Amelia Hana Salsabila; Dian Kartika Prabaningrum (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Education is the influence given by adults to immature people, in this case the education given by teachers to children in order to help their development. The characteristics of the development of children in the early grades of elementary school are early childhood. Even though early childhood is a short period of growth for children, this period is a very important period in their lives. Therefore, it is necessary to encourage all children's potential during this period so that they can develop optimally. The development of first, second and third grade students is marked by mature physical growth and the ability to control the body and maintain balance. The intellectual development of children in the early elementary grades includes the ability to arrange and group objects, the ability to take an interest in numbers and letters, the ability to increase vocabulary, the ability to enjoy talking, the ability to understand cause and effect. effects, and is evident in the ability to develop an understanding of things. space and time.